Cooperative Assembly of 2D-MOF Nanoplatelets into Hierarchical Carpets and Tubular Superstructures for Advanced Air Filtration - Schwotzer, Friedrich; Horak, Jacob; Senkovska, Irena; Schade, Elke; Gorelik, Tatiana E.; Wollmann, Philipp; Anh, Mai Le; Ruck, Michael; Kaiser, Ute; Weidinger, Inez M.; Kaskel, Stefan (Angewandte Chemie International Edition, 2022)
Clean air is an indispensable prerequisite for human health. The capture of small toxic molecules requires the development of advanced materials for air filtration. Two-dimensional nanomaterials offer highly accessible surface areas but for real-world applications their assembly into well-defined hierarchical mesostructures is essential. DUT-134(Cu) ([Cu2(dttc)2]n, dttc=dithieno[3,2-b : 2′,3′-d]thiophene-2,6-dicarboxylate]) is a metal–organic framework forming platelet-shaped particles, that can be organized into complex structures, such as millimeter large free-standing layers (carpets) and tubes. The structured material demonstrates enhanced accessibility of open metal sites and significantly enhanced H2S adsorption capacity in gas filtering tests compared with traditional bulk analogues.
CRIS-Team Scopus Importer:2022-04-14
Keywords: 2D Material; Air Filtration; Chemisorption; Mesocrystal; Metal–Organic Frameworks; Self-Assembly